Agile Development with ICONIX Process People, Process, and Pragmatism - Rosenberg, Don. (Apress : Imprint: Apress, 2005)
This book describes how to apply ICONIX Process (a minimal, use case-driven modeling process) in an agile software project. It's full of practical advice for avoiding common agile pitfalls. Further, the book defines a core agile subset so those of you who want to get agile need not spend years learning to do it. Instead, you can simply read this book and apply the core subset of techniques. The book follows a real-life .NET/C# project from inception and UML modeling, to working code through several iterations. You can then go on-line to compare the finished product with the initial set of use cases. The book also introduces several extensions to the core ICONIX Process, including combining test-driven development (TDD) with up-front design to maximize both approaches (with examples using Java and JUnit). And the book incorporates persona analysis to drive the projects goals and reduce requirements churn.